Sistem Pendukung Keputusan Berbasis Logika Kabur Untuk Penyeleksian Pelamar Beasiswa Dengan Metode Sugeno "Beaflogeno" - Kurnianto, Achmad; , Heru Supriyono, ST. MSc. PhD (2017)
Scholarship is an educational funding from an agency that is given to the institution or university that aims to help students college who underprivileged and achievement. In today's world of education, almost all students becomes frequently searching scholarship in educational institution. Problems in the selection of the scholarship is passing important variables when selecting applicants and the number of scholarships that cause the process from start registration until publication of the selection results to be very long and requires human resources relatively large. This research aims to create a web-based system based on fuzzy logic to simplify the selection of scholarship efficiency gains time and human resources, and avoid social bias and accountable. The method used for this study is the method Sugeno fuzzy logic. Where important variables incorporated into the calculation of SIFS (Sugeno Fuzzy Inference System). Then the result will be a recommendation. The system is built with the programming language python with django framework. The method of this research use waterfall method. The products of this research is a web application decision support system based on fuzzy logic Sugeno method for receiving a scholarship. Testing system use blackbox. Then, the result of the testing is good. For validation testing get 92,3% success, and error get 7,7%. And then, the last testing is UAT testing get 78% agree and interesting with the system.